Proanthocyanidins-induced horizontal arrangement poly(vinyl alcohol)/graphene composites with enhanced mechanical properties - Wang, Chao; Wen, Min; Guo, Le; Zhang, Boyu; Ming, Tingzhen; Huang, Fuzhi; Zhang, Qi (Wiley, 2019)
A green approach is employed to prepare mechanically enhanced composites by adding noncovalently proanthocyanidin (PC)‐modified graphene (PC‐rGO) into poly(vinyl alcohol) (PVA). Ascorbic acid (AA) is used as the reducing agent, and PC is used as a dispersant to synthesize low‐defect and fully dispersed graphene. After static treatment, the PC‐rGO sheets in the composite form a horizontally arranged structure. Compared with neat PVA, the Young's modulus of the graphene‐modified composites is significantly enhanced by approximately 79.3% with incorporation of 0.9 wt% PC‐rGO. The composites incorporated with GO or AA‐rGO (without PC) have randomly distributed GO structures and apparent rGO agglomeration, resulting in a weaker mechanical property. The dispersibility, degree of defects, distribution state of graphene, and interactions with the polymer matrix are directly related to the final mechanical performance. This new approach to mechanically enhance graphene‐embedded PVA composites provides the possibility for large‐scale production of graphene‐reinforced composite materials.